PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN ( PNPM-MP) EKONOMI BERGULIR KELOMPOK DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU - SULASTRI "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PNPM MP is independent urban constitute to process changing one expected of condition of society which over a barrel, as free as unattached on something that wills be civic society. agglomerate economic activity unsecured seeds money added fund and also launching forth for revenue enhancement indigent society. Present programs PNPM MP matter for society hole in the wall seed money increase. Since supervisory reducing of managing PNPM MP nots borrower want to back PNPM MP loan installment and PNPM MP'S fund loan incorrectly target which necessarily indigent society that utilizes to lent fund is not economic society good. As about problem: one that PNPM MP'S performing? And there is factor even funds unsecured failing economic agglomerate go delinquent one?This research intent to know performing form PNPM MP at Kelurahan Sail. Any kind unsecured failing factors funds. Observational type is simple random is sampling with deskritif's quantitative approaching. Data requirement cover acquired primary data through koesioner's inlay result and secondary. Total population 62 arrearses and sample amount 31 person.Of research result can know to mark sense target fault hit PNPM MP fund lending its reducing observation, socialization, monitoring, checking hits effort of organizer. Meanwhile of bust causal factor fund borrower effort which is carried on not walking, donation money assumption, abilities inappropriate effort, no wish refunds and its reducing to agglomerate solidarity.Key word: PNPM MP performing, motivation and failing factors